THE INFLUENCE OF BOLUS TRIGGERING ACTIVATION DELAY TO RADIATION DOSE AT CT SCAN EXAMINATION OF THE THORAX IN RADIOLOGY OF Dr. MOEWARDI HOSPITAL - Indrati, Rini; Mariyatun, Mariyatun; Kurniawan, Andrey Nino (Jurnal Imejing Diagnostik, 2015)
Background : Examination of Thorax CT Scan in RSUD Dr.Moewardi is always conducted using bolus triggering technique, where delay of bolus triggering activation done to vary value between 5 - 10 second after contrast media administration using automatic injector with the reason to lessen radiation dose. Purpose of this research is to know influence of  bolus triggering activation delay to radiation dose as well as  to find out  maximal delay value of  bolus triggering activation delay which can be conducted at CT Scan Thorax examination.Methods : This research is experimental method. Data were collected from the observations and the direct examinations on the monitor screen using the CTDIvol dose calculation software. This research is carried out by recording the changes radiation dose value on CTDIvol by changing the value of  bolus triggering activation delay from 0, 2, 4,  6, 8, 10, 12 and 14 second. Data were analyzed using regression test.Results : The result shows that correlation between bolus triggering activation delay towards radiation dose with r = 0,970,  p value < 0,001 and R2 = 0,940. The meaning 94% radiation dose influenced by bolus triggering activation. Delay with regresi equation, Y  = 308,252 - 18,821 DT, showing each every increase of delay bolus triggering activation delay equal to 1 second  will influence to descend dose radiasi equal to 18,821 mGy.Conclusion : Maximum delay to activated bolus triggering is 17 second.